Policies and Practices of Teachers' Professional Development from a Lifelong Learning Perspective (Journal of Education, Humanities, and Social Research, 2025)
Teachers are key practitioners in unlocking the potential of each learner and achieving inclusive and equitable quality education. According to the 2023 Global Teacher Report, there remains a global shortage of teachers, which threatens the future of education. In order to ensure both the quantity and quality of the teaching workforce, it is necessary to reexamine teachers' professional development from the perspective of lifelong learning, strengthening their dual role as lifelong learners and leaders of lifelong learning. This will help establish a new social contract for the teaching profession. Based on the dual evolution of global development trends and historical policy work, the UNESCO Institute for Lifelong Learning (UIL) and Shanghai Normal University jointly organized the "Teachers as Lifelong Learners: Policy and Practice International Research Seminar". The seminar aimed to explain the rich connotations and key features of lifelong learning, share policies and practices on continuous professional development for teachers in various countries, and provide theoretical guidance and practical experience for teachers' professional development. Although approaches such as policy support, institutional backing, technological empowerment, and research-led initiatives have become international consensus and action for supporting teachers' professional development, facing both macro-level societal challenges and micro-level educational field challenges, continuous deepening of international exchange and cooperation is still needed to promote teachers' lifelong learning and continuous professional development.